Curable resin composition, adhesive, sealing material, cured product, semiconductor device and electronic component

By adding specific organic peroxides and inorganic particles to the resin composition, the problem of difficult curing of traditional resin compositions at low temperatures is solved, and the effect of rapid curing and prolonging the application period at low temperatures of 50-100°C is achieved. It is suitable for adhesives and sealing materials in IoT applications.

CN119894942APending Publication Date: 2025-04-25NAMICS CORPORATION
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202380068729.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-11-24
Filing Date
2023-09-21
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The prior art is difficult to cure curable resin compositions at low temperatures, especially in IoT applications such as smartphones. Traditional thermal radical polymerized resin compositions require high temperature conditions and have a short application period.

Method used

By adjusting the composition and structure, curing at a low temperature of 50 to 100°C, preferably 80°C, and extending the applicable period by using a resin composition containing a curable compound of radical polymerization, inorganic particles and an organic peroxide having a dicarbonate structure.

Benefits of technology

A curable resin composition that cures rapidly at low temperatures is achieved, extends its applicable life, and provides an appropriate modulus of elasticity at room temperature, making it suitable for the manufacturing of semiconductor devices and electronic components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119894942A_ABST
    Figure CN119894942A_ABST
Patent Text Reader

Abstract

The present invention addresses the problem of providing: a curable resin composition which can be cured at a low temperature of, for example, 50-100 DEG C, preferably 80 DEG C, and which has a long pot life; and an adhesive. Provided is a curable resin composition comprising (A) a radically polymerizable curable compound, (B) inorganic particles, and (C) an organic peroxide having a dicarbonate structure represented by formula (1). In formula (1), R1 and R2 are each independently an alkyl group having at least 11 carbon atoms. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a curable resin composition, an adhesive or a sealing material containing the same, a cured product thereof, and a semiconductor device and an electronic component containing the cured product thereof. Background Art

[0002] As high-function communication terminals such as smartphones and tablets become more popular, the demand for lightweight, miniaturized, and thinner products is increasing. In addition, the market for IoT (Internet of Things), where all objects are connected to the Internet, is growing rapidly. In the process of developing various devices for IoT applications including smartphones, the inability to manufacture at high temperatures due to problems with components has become an issue. For example, the joining of components using solder requires joining at a high temperature of more than 180°C, which will damage the components, so there is a need for joining materials that can be joined by curing at low temperatures.

[0003] Thermal radical polymerizable resin compositions used in methods for manufacturing electronic component devices and semiconductor devices are known. For example, Patent Document 1 discloses a pre-feed bottom filling material comprising a radical polymerizable compound of a specific structure, a radical polymerization initiator, an inorganic filler, and a flexible agent of a specific structure. Patent Document 2 discloses a conductive resin composition and a chip mounting agent comprising the same, characterized in that the composition comprises (A) a polyethylene glycol di(meth)acrylate of a specific structure, (B) a radical generator, (C) a conductive filler, and (D) at least one selected from a linear alkanediol di(meth)acrylate having a linear alkylene group having 5 to 14 carbon atoms, a monofunctional and bifunctional polyester (meth)acrylate, and a terminal-modified polybutadiene rubber.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2020-065063

[0007] Patent Document 2: Japanese Patent Application Publication No. 2016-117860 Summary of the invention

[0008] Problems to be solved by the invention

[0009] Curable resin compositions for adhesives used in IoT applications such as smartphones, for example, camera modules, are required to be curable at low temperatures of 80° C. or lower. In addition, resin compositions for adhesives are required to have a long pot life and good storage stability.

[0010] The pre-applied underfill material disclosed in Patent Document 1 requires a high temperature treatment of 150 to 350° C. during thermal curing. In addition, the conductive resin composition disclosed in Patent Document 2 also requires a treatment at a temperature of about 150° C. during thermal curing.

[0011] In order to enable the thermal radical polymerizable resin composition to be cured at low temperature, a large amount of a highly reactive radical initiator may be used. In this case, the curing reaction may proceed at an undesirable temperature, and the pot life may be shortened.

[0012] An object of the present invention is to provide a curable resin composition and an adhesive which can be cured at a low temperature of, for example, 50 to 100° C., preferably 80° C., and have a long pot life.

[0013] Means for solving problems

[0014] Specific means for solving the above-mentioned problems are as follows.

[0015] A first embodiment of the present invention is the following resin composition.

[0016] (1) A curable resin composition comprising:

[0017] (A) a free radical polymerizable curable compound;

[0018] (B) inorganic particles; and

[0019] (C) An organic peroxide having a dicarbonate structure represented by the following formula (1).

[0020] [Chemical formula 1]

[0021]

[0022] In the above formula (1), R1 and R2 are each independently an alkyl group having at least 11 carbon atoms.

[0023] (2) The curable resin composition according to (1) above, wherein the weight average molecular weight of the organic peroxide (C) is 400 or more.

[0024] (3) The curable resin composition according to (1) or (2) above, wherein the (C) organic peroxide has a 10-hour half-life temperature of 70° C. or less.

[0025] (4) The curable resin composition according to any one of (1) to (3) above, wherein the content of the (C) organic peroxide is 0.1 to 30 parts by mass based on 100 parts by mass of the (A) radically polymerizable curable compound.

[0026] (5) The curable resin composition according to any one of (1) to (4) above, wherein the (A) radically polymerizable curable compound comprises a (meth)acrylate compound.

[0027] (6) The curable resin composition according to any one of (1) to (5) above, wherein the (A) radically polymerizable curable compound comprises a urethane (meth)acrylate compound.

[0028] (7) The curable resin composition according to any one of (1) to (6) above, wherein the (A) radically polymerizable curable compound comprises a bismaleimide compound.

[0029] (8) The curable resin composition according to any one of (1) to (7), wherein the (B) inorganic particles include conductive particles.

[0030] (9) The curable resin composition according to any one of (1) to (8) above, further comprising (D) a polymerization inhibitor.

[0031] A second aspect of the present invention is (10) an adhesive or a sealing material comprising the curable resin composition according to any one of (1) to (9) above.

[0032] The third embodiment of the present invention is the following cured product.

[0033] (11) A cured product obtained by curing the curable resin composition according to any one of (1) to (9) above, or the adhesive or sealing material according to (9) above.

[0034] (12) The cured product according to (11) above, wherein the room temperature elastic modulus of the cured product obtained by curing at 80° C. for 60 minutes is 0.01 to 8.0 GPa.

[0035] A fourth aspect of the present invention is (13) a semiconductor device or an electronic component including the cured product described in (11) or (12) above.

[0036] Effects of the Invention

[0037] According to the first embodiment of the present invention, a curable resin composition that can be cured at a low temperature of, for example, 50 to 100°C, preferably 80°C, and has a long shelf life can be provided. In addition, according to the second embodiment of the present invention, an adhesive or sealing material that can be cured at a low temperature of, for example, 50 to 100°C, preferably 80°C, and has a long shelf life can be provided. In addition, according to the third embodiment of the present invention, a cured product that has an appropriate room temperature elastic modulus depending on the application and is useful as a conductive material or an insulating material can be provided. According to the fourth embodiment of the present invention, a semiconductor device and an electronic component that include a cured product that has an appropriate room temperature elastic modulus depending on the application and is useful as a conductive material or an insulating material can be provided. DETAILED DESCRIPTION

[0038] In this specification, in accordance with the customary practice in the field of synthetic resins, a name including the term "resin" generally referring to a polymer (particularly a synthetic polymer) is sometimes used for a component constituting a curable resin composition before curing, even though the component is not a polymer.

[0039] In this specification, the general term "pot life" refers to the time during which a resin composition can be used after it is produced. In the examples described below, the change ratio of the viscosity of the resin composition after it is left for a predetermined time is calculated as the viscosity increase ratio when the viscosity of the resin composition just produced is set to 1.0, and the time when the viscosity increase ratio reaches 1.5 times or more is the pot life (unit: hours) of the resin composition.

[0040] In the present specification, the term "(meth)acryloyl group" includes both a methacryloyl group and an acryloyl group. In addition, the term "(meth)acrylate compound" includes both an acrylate compound and a methacrylate compound.

[0041] In this specification, the weight average molecular weight refers to a value obtained by gel permeation chromatography (GPC) using a calibration curve based on standard polystyrene.

[0042] In this specification, the average particle size (D50) of inorganic particles including conductive particles and insulating particles refers to a particle size (median diameter) having a cumulative frequency of 50% in a volume-based particle size distribution measured by a laser diffraction-scattering method.

[0043] [Resin composition]

[0044] The curable resin composition according to the first embodiment of the present invention includes:

[0045] (A) a free radical polymerizable curable compound;

[0046] (B) inorganic particles; and

[0047] (C) an organic peroxide having a dicarbonate structure represented by the following formula (1),

[0048] [Chemical formula 2]

[0049]

[0050] In the above formula (1), R1 and R2 are each independently an alkyl group having at least 11 carbon atoms. According to this embodiment, a curable resin composition can be provided which can be cured at a low temperature of, for example, 50 to 100° C., preferably 80° C., and has a long pot life.

[0051] (A) Radically polymerizable curable compound

[0052] The resin composition of the present embodiment includes (A) a radically polymerizable curable compound (hereinafter, also referred to as "component (A)"). The radically polymerizable curable compound (A) imparts curability and adhesiveness to the resin composition. The radically polymerizable curable compound (A) can be cured rapidly because of its high polymerization rate. The radically polymerizable curable compound (A) is not particularly limited as long as it has radical polymerizability, and examples thereof include, but are not limited to, (meth)acrylate compounds, bismaleimide compounds, and the like.

[0053] In the present embodiment, (A) the radical polymerizable curable compound preferably includes at least one selected from (meth)acrylate compounds and bismaleimide compounds, and may also include two. In a certain embodiment, (A) the radical polymerizable curable compound preferably includes a (meth)acrylate compound. (Meth)acrylate compounds include carbamate (meth)acrylate compounds, and in a certain embodiment, (A) the radical polymerizable curable compound preferably includes a carbamate (meth)acrylate compound. In a certain embodiment, (A) the radical polymerizable curable compound preferably includes a bismaleimide compound. In one embodiment, the (A) radically polymerizable curable compound may include, for example, a (meth)acrylate compound other than a urethane (meth)acrylate compound alone, may include two types of a (meth)acrylate compound other than a urethane (meth)acrylate compound and a urethane (meth)acrylate compound, may include two types of a (meth)acrylate compound other than a urethane (meth)acrylate compound and a bismaleimide compound, or may include three types of a (meth)acrylate compound other than a urethane (meth)acrylate compound, a bismaleimide compound, and a urethane (meth)acrylate compound.

[0054] In one embodiment, the radical polymerizable curable compound (A) is preferably in a liquid state at 25° C. Thus, no solvent is required in the resin composition, and thus the generation of voids when the resin composition is used can be prevented. The content of the solvent in the resin composition of the present embodiment is preferably less than 3% by mass, more preferably less than 1% by mass, and further preferably 0% by mass (solvent-free) relative to the total mass of the resin composition.

[0055] The content of the radically polymerizable curable compound (A) in the resin composition is preferably 4 to 90 parts by mass, more preferably 5 to 50 parts by mass, and even more preferably 7 to 30 parts by mass, relative to 100 parts by mass of the total amount of the resin composition. In addition, the content of the radically polymerizable curable compound (A) in the resin composition is preferably 75 to 99 parts by mass, more preferably 80 to 98 parts by mass, even more preferably 85 to 97 parts by mass, and particularly preferably 90 to 97 parts by mass, relative to 100 parts by mass of the total amount of all organic substances contained in the resin composition.

[0056] The (meth)acrylate compound only needs to have at least one (meth)acryloyl group in the molecule, and examples thereof include monofunctional (meth)acrylate compounds having one (meth)acryloyl group and polyfunctional (meth)acrylate compounds having two or more (meth)acryloyl groups. Examples of the monofunctional (meth)acrylate compound include alkyl (meth)acrylates having a branched alkyl group such as isobutyl (meth)acrylate and tert-butyl (meth)acrylate; esters of (meth)acrylic acid and alicyclic alcohols such as cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, and dicyclopentanyl (meth)acrylate; esters of (meth)acrylic acid and cyclic alcohols such as cyclic trimethylolpropane methylal (meth)acrylate; esters of (meth)acrylic acid and aromatic alcohols such as phenoxyethyl (meth)acrylate; acid-modified mono(meth)acrylates such as phosphoric acid-modified (meth)acrylate; and (meth)acrylamide compounds such as hydroxyethyl (meth)acrylamide, but the present invention is not limited thereto. Examples of the multifunctional (meth)acrylate compound include alkyl (meth)acrylates such as 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, and neopentyl glycol di(meth)acrylate; polyalkylene glycol di(meth)acrylates such as tripropylene glycol di(meth)acrylate; difunctional (meth)acrylates such as polyester (meth)acrylate and neopentyl glycol-modified trimethylolpropane di(meth)acrylate; and trimethylolpropane tri(meth)acrylate. The present invention also includes trifunctional (meth)acrylates such as pentaerythritol tetra(meth)acrylate and di(trimethylolpropane) tetra(meth)acrylate; pentafunctional (meth)acrylates such as dipentaerythritol penta(meth)acrylate; (meth)acrylates containing a cyclic structure such as dihydroxymethyl-tricyclodecane di(meth)acrylate; acid-modified poly(meth)acrylates such as phosphoric acid-modified poly(meth)acrylate; urethane (meth)acrylates having a urethane bond and a (meth)acryloyl group, etc., but is not limited to these. In a certain embodiment, when the cured product of the resin composition is required to have flexibility, the multifunctional (meth)acrylate compound preferably has a linear alkylene skeleton with 4 or more carbon atoms or a linear oxyalkylene skeleton with 4 or more carbon atoms between adjacent (meth)acryloyl groups. In a certain embodiment, when the cured product of the resin composition is required to have flexibility, the multifunctional (meth)acrylate compound is preferably a difunctional (meth)acrylate compound.

[0057] In a certain embodiment, from the viewpoint of workability of the resin composition, the (meth)acrylate compound preferably includes a monofunctional (meth)acrylate compound. In a certain embodiment, from the viewpoint of improving reactivity, the (meth)acrylate compound preferably includes a polyfunctional (meth)acrylate compound. In a certain embodiment, the (meth)acrylate compound preferably includes a monofunctional (meth)acrylate compound and a polyfunctional (meth)acrylate compound. In a certain embodiment, the (meth)acrylate compound preferably includes a monofunctional (meth)acrylate compound and a difunctional (meth)acrylate compound.

[0058] In a certain embodiment, when the cured product of the resin composition is required to have flexibility, the (meth)acrylate compound preferably includes a (meth)acrylate compound having a glass transition temperature (Tg) of 15°C or less. In a certain embodiment, from the viewpoint of suppressing the curing inhibition caused by oxygen on the surface of the cured product and the tackiness (stickiness) caused by it, the (meth)acrylate compound preferably includes a (meth)acrylate compound having a glass transition temperature (Tg) exceeding 15°C. In a certain embodiment, the (meth)acrylate compound preferably includes a (meth)acrylate compound having a glass transition temperature (Tg) of 15°C or less and a (meth)acrylate compound having a glass transition temperature (Tg) exceeding 15°C. In the present specification, the glass transition temperature (Tg) of the (meth)acrylate compound can be set as the glass transition temperature (Tg) when it is made into a homopolymer, and measured using a dynamic viscoelasticity measuring device (DMA). The glass transition temperature (Tg) of the (meth)acrylate compound was measured using a dynamic viscoelasticity analyzer (DMA) in a tensile mode, a frequency of 10 Hz, and a heating temperature of 3° C. / min. The peak of the obtained tan δ graph was defined as the glass transition temperature.

[0059] As the (meth)acrylate compound, any one kind may be used, or two or more kinds may be used in combination.

[0060] When the component (A) contains a (meth)acrylate compound, the content of the (meth)acrylate compound is preferably 3 to 100 parts by mass, more preferably 5 to 80 parts by mass, and even more preferably 8 to 75 parts by mass based on 100 parts by mass of the component (A), from the viewpoint of workability of the resin composition, adhesion and tack-free property of the cured product.

[0061] (Meth)acrylate compounds include urethane (meth)acrylate compounds. Depending on the properties required of the cured product, component (A) may contain urethane (meth)acrylate compounds. Urethane (meth)acrylate compounds are oligomers having urethane bonds and (meth)acryloyl groups, and can be obtained by the reaction of hydroxyl groups and isocyanate groups of three components, hydroxy (meth)acrylate, diisocyanate and polyol, as the main raw materials. By combining the main raw materials, various properties can be imparted to the obtained urethane (meth)acrylate compounds. For example, when the polyol as the main raw material is an ether compound, the hydrolysis resistance and flexibility are excellent. For example, when the polyol as the main raw material is an ester compound, the heat resistance, flexibility and toughness are excellent. For example, when the polyol as the main raw material is a carbonate compound, the heat resistance, weather resistance and toughness are excellent.

[0062] The weight average molecular weight of the urethane (meth) acrylate compound is preferably 1,600 to 20,000, more preferably 2,000 to 18,000, and further preferably 3,000 to 15,000. Among them, from the viewpoint of workability and reactivity of the resin composition, the urethane (meth) acrylate compound preferably does not substantially contain a urethane (meth) acrylate compound having a weight average molecular weight exceeding 20,000. In addition, the urethane (meth) acrylate compound preferably does not substantially contain a urethane (meth) acrylate compound having a weight average molecular weight of less than 1,600. It should be noted that, when used in this specification, "substantially free of" means that the component is not intentionally included, specifically, it means that the component is present in an amount of less than 0.1% by mass in the curable resin composition.

[0063] The urethane (meth)acrylate compounds may be used alone or in combination of two or more.

[0064] When component (A) contains a urethane (meth)acrylate compound, the content of the urethane (meth)acrylate compound is preferably 5 to 75 parts by mass, more preferably 6 to 50 parts by mass, and even more preferably 7 to 30 parts by mass, based on 100 parts by mass of component (A).

[0065] When reliability (heat resistance, moisture resistance) and adhesion strength are required for the cured product, component (A) preferably contains a bismaleimide compound. The bismaleimide compound is not particularly limited, and any compound having a chemical structure sandwiched by two maleimide groups can be used. Examples of bismaleimide compounds include N,N'-(4,4'-diphenylmethane)bismaleimide, bisphenol A diphenyl ether bismaleimide, 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane bismaleimide, 4-methyl-1,3-phenylene bismaleimide, 1,6'-bismaleimide-(2,2,4-trimethyl)hexane, bis-(3-ethyl-5-methyl-4-maleimidephenyl)methane, meta-phenylene bismaleimide. imide (N,N'-1,3-phenylenebismaleimide), 1,6-bismaleimide hexane, 1,2-bismaleimide ethane (N,N'-ethylenebismaleimide), N,N'-(1,2-phenylene)bismaleimide, N,N'-1,4-phenylene dimaleimide, N,N'-(sulfonyl di-p-phenylene) dimaleimide, N,N'-[3,3'-(1,3-phenylenedioxy) diphenyl] bismaleimide, but not limited to these.

[0066] In the case where a low elastic modulus at room temperature is required for the cured product of the resin composition, the bismaleimide compound is preferably a bismaleimide compound having a hydrocarbon group derived from a dimer acid. Such a bismaleimide compound is described, for example, in Japanese Patent Publication No. 2015-193725. The hydrocarbon group derived from the dimer acid does not have a crosslinking reactive group in the molecular chain, so it is believed that the elastic modulus at room temperature can be reduced. As a commercially available product of a bismaleimide compound having a hydrocarbon group derived from a dimer acid, for example, a product name "BMI-1500" and a product name "BMI-1700" which are liquid at 25°C, or a product name "BMI-3000" which is solid at 25°C (all manufactured by Designer Molecules Inc.), but is not limited to these.

[0067] The bismaleimide compound may be liquid or solid at 25° C., but is preferably liquid at 25° C. The weight average molecular weight of the bismaleimide compound is preferably 500 to 7,000, more preferably 700 to 5,500, and even more preferably 800 to 3,000.

[0068] The bismaleimide compounds may be used alone or in combination of two or more.

[0069] When component (A) contains a bismaleimide compound, the content of the bismaleimide compound is preferably 5 to 40 parts by mass, more preferably 15 to 35 parts by mass, based on 100 parts by mass of component (A).

[0070] (B) Inorganic particles

[0071] The resin composition of the present embodiment contains (B) inorganic particles (hereinafter, also referred to as "component (B)"). The inorganic particles are, for example, (B1) conductive particles, (B2) insulating particles, and the like.

[0072] (B1) Conductive particles are used to impart thermal conductivity and / or electrical conductivity to the resin composition and its cured product. The resin composition containing (B1) conductive particles can also be used as a conductive adhesive used in the bonding of electronic components and the like. In the present specification, "conductive particles" means particles having an average particle diameter in the range of 0.01 μm to 100 μm and an electrical conductivity of 10 6 S / m or more. (B1) Conductive particles may be particles formed by shaping a conductive substance into a particle shape, or particles coated with a conductive substance on a core (core particles) (coated powder). Regarding the core contained in the conductive particles, as long as a part thereof is coated with a conductive substance, it may be formed of a non-conductive substance. (B1) Conductive particles include metal powders and coated powders.

[0073] The conductive substance in (B1) conductive particles is not particularly limited as long as it is a substance that imparts thermal conductivity and / or electrical conductivity to the resin composition. Examples thereof include gold, silver, nickel, copper, palladium, platinum, bismuth, tin, and their alloys (especially bismuth-tin alloys, solders, etc.), aluminum, indium tin oxide, silver-coated copper, silver-coated aluminum, metal-coated glass beads, silver-coated fibers, silver-coated resins, antimony-doped tin, tin oxide, carbon fibers, graphite, carbon black, and mixtures thereof, but are not limited thereto. From the viewpoints of good thermal conductivity and electrical conductivity, the conductive substance in (B1) conductive particles is preferably at least one metal selected from silver, nickel, copper, tin, aluminum, silver alloys, nickel alloys, copper alloys, and aluminum alloys, more preferably at least one metal selected from silver, copper, and nickel, further preferably silver or copper, and particularly preferably contains silver. In one aspect, (B1) conductive particles are preferably silver particles. In one aspect, (B1) conductive particles are preferably copper particles. Silver particles or copper particles include silver powder or copper powder, and coated powders obtained by coating at least a part of the surface of a core (core particles) with silver or copper, respectively.

[0074] (B1) The shape of the conductive particles is not particularly limited, and may be any shape including spherical, amorphous, flaky (scaly), filamentous (needle-shaped), dendritic, etc. Flaky refers to a shape having an aspect ratio of 2 or more represented by "major diameter / minor diameter", and includes flat plate shapes such as plate-like and flaky. In this specification, the major diameter and minor diameter of the conductive particles refer to the average value of the major diameter and minor diameter of any 20 particles based on an image obtained by a scanning electron microscope (SEM). "Major diameter" refers to the diameter with the longest distance in a line segment passing through the approximate center of gravity of the particle in the particle image obtained by SEM, and "minor diameter" refers to the diameter with the shortest distance in a line segment passing through the approximate center of gravity of the particle in the particle image obtained by SEM. (B1) The conductive particles may contain particles of different shapes.

[0075] When the conductive particles (B1) are silver particles, the tap density of the silver particles is preferably 1.5 g / cm from the viewpoint of dispersibility. 3 More preferably, 2.0 to 6.0 g / cm 3 In this specification, the tap density is a value measured in accordance with JIS Z2512 Metal powder-tap density measurement method.

[0076] When the conductive particles (B1) are silver particles, the average particle size (D50) is preferably 0.05 to 50 μm, more preferably 0.1 to 20 μm, and even more preferably 0.1 to 15 μm, from the viewpoint of the fluidity of the resin composition and the conductivity of the cured product.

[0077] When the conductive particles (B1) are silver particles, the BET specific surface area is preferably 4.0 m 2 / g or less, more preferably 0.1 to 3.0 m 2 / g.

[0078] (B1) The conductive particles may be used alone or in combination of two or more.

[0079] The content of the conductive particles (B1) in the resin composition is, for example, 95 parts by mass or less, for example, 92 parts by mass or less, relative to 100 parts by mass of the total amount of the resin composition. In one embodiment, the content of the conductive particles (B1) in the resin composition is preferably 10 to 95 parts by mass, more preferably 20 to 95 parts by mass, further preferably 50 to 95 parts by mass, and may be 70 to 95 parts by mass, relative to 100 parts by mass of the total amount of the resin composition.

[0080] The insulating particles (B2) can reduce the linear expansion coefficient of the cured product obtained by curing the resin composition, thereby improving heat cycle resistance. The resin composition containing the insulating particles (B2) can also be used as an insulating adhesive or sealing material used for bonding and protecting electronic components.

[0081] (B2) insulating particles are not particularly limited as long as they contain granules formed of insulating inorganic materials and have the effect of reducing the linear expansion coefficient by addition. As insulating inorganic materials, silicon dioxide, talc, aluminum oxide, aluminum nitride, calcium carbonate, aluminum silicate, magnesium silicate, magnesium carbonate, barium sulfate, barium carbonate, calcium sulfate (Japanese: lime sulfate), aluminum hydroxide, calcium silicate, potassium titanate, titanium oxide, zinc oxide, silicon carbide, silicon nitride, boron nitride, etc. can be used. As (B2) insulating particles, silicon dioxide particles are preferably used from the aspect of being able to increase the filling amount. Silica is preferably amorphous silicon dioxide. Regarding (B2) insulating particles, their surfaces can be surface treated with a coupling agent such as a silane coupling agent.

[0082] The shape of the insulating particles (B2) is not particularly limited, and may be any of spherical, irregular, flake (scaly), filamentous (needle), dendritic, and the like.

[0083] When the insulating particles (B2) are silica particles, the average particle size (D50) thereof is preferably 0.01 to 20 μm, more preferably 0.05 to 15 μm, and even more preferably 0.1 to 10 μm.

[0084] (B2) The insulating particles may be used alone or in combination of two or more.

[0085] The content of the insulating particles (B2) is preferably 0.1 to 80 parts by mass, more preferably 1 to 75 parts by mass, and even more preferably 10 to 70 parts by mass, based on 100 parts by mass of the total amount of the resin composition.

[0086] (C) An organic peroxide having a dicarbonate structure represented by formula (1)

[0087] The resin composition of the present embodiment contains (C) an organic peroxide having a dicarbonate structure represented by the following formula (1) (hereinafter also referred to as “component (C)”).

[0088] [Chemical formula 3]

[0089]

[0090] In the above formula (1), R1 and R2 are each independently an alkyl group having at least 11 carbon atoms. The alkyl group may be any of a linear, branched or cyclic group, and may also be any combination thereof. R1 and R2 may be the same or different. The number of carbon atoms of the alkyl group represented by R1 and R2 is preferably 11 to 30, more preferably 11 to 20, and further preferably 12 to 20. In a certain embodiment, the alkyl group is preferably linear. In addition, component (C) is preferably solid at 25°C. The average particle size of component (C) is preferably 1μm to 400μm. Here, the average particle size refers to the value of the volume cumulative 50% particle size (D50), and is a value obtained based on the volume-based particle size distribution measured using a laser diffraction particle size distribution measuring device and a measuring device based on a dynamic light scattering method.

[0091] Generally, organic peroxides generate active free radicals by cleavage at a predetermined temperature. The free radical polymerization reaction of the radical polymerizable curable compound is initiated by the active free radicals. However, if a highly reactive free radical initiator is used in large quantities in order to enable curing at low temperatures, the curing reaction may sometimes proceed at an undesirable temperature, shortening the pot life. Since component (C) has a dicarbonate structure, it efficiently generates free radicals at low temperatures of, for example, 50 to 100°C, preferably 80°C, and is not prone to termination reactions of free radical deactivation, thereby allowing the initiation reaction and growth reaction of the radical polymerization reaction of the resin composition to proceed efficiently. On the other hand, since component (C) has side chains R1 and R2 with large molecular weights, component (C) has a large activation energy and is more stable at room temperature (e.g., about 25°C) when stored. By including component (C), a curable resin composition that can be cured at low temperatures of 50 to 100°C and has a long pot life can be provided.

[0092] From the viewpoint of better stability, the weight average molecular weight of component (C) is preferably 400 or more, more preferably 450 or more, and even more preferably 500 or more. The upper limit of the weight average molecular weight of component (C) is not particularly limited, and is, for example, 1500 or less, 1200 or less, or 1000 or less.

[0093] The 10-hour half-life temperature (T10) of the component (C) is preferably 70° C. or lower, more preferably 35 to 70° C., and even more preferably 40 to 70° C. The 10-hour half-life temperature (T10) of the component (C) of 70° C. or lower is an index indicating the radical generating ability of the component (C) at a low temperature of 50 to 100° C. and the stability at room temperature.

[0094] The component (C) may be used alone or in combination of two or more.

[0095] The content of the component (C) in the resin composition is preferably 0.1 to 30 parts by mass, more preferably 1 to 20 parts by mass, and even more preferably 3 to 10 parts by mass, based on 100 parts by mass of the radically polymerizable curable compound (A).

[0096] The resin composition of the present embodiment may contain, as necessary, any component other than the above-mentioned components (A) to (C), for example, the components described below.

[0097] (D) Inhibitor

[0098] The resin composition of the present embodiment may also contain (D) a polymerization inhibitor (hereinafter also referred to as "component (D)"). The (D) polymerization inhibitor is a compound having a free radical capture ability. By containing the (D) polymerization inhibitor, the progress of an undesirable free radical polymerization reaction at room temperature of about 25° C. can be suppressed, and the stability of the resin composition during storage can be further improved.

[0099] As the polymerization inhibitor (D), a known polymerization inhibitor can be used, and examples thereof include, but are not limited to, N-nitroso-N-phenylhydroxylamine aluminum, triphenylphosphine, p-methoxyphenol, hydroquinone, p-benzoquinone, and the like. In addition, known polymerization inhibitors disclosed in Japanese Patent Application Laid-Open No. 2010-117545 and Japanese Patent Application Laid-Open No. 2008-184514 can also be used. Any one of the polymerization inhibitors (D) can be used, or two or more of them can be used in combination.

[0100] When the resin composition contains (D) a polymerization inhibitor, the content of the (D) polymerization inhibitor is preferably 0.1 to 5.0 parts by mass, more preferably 0.2 to 4.0 parts by mass, and even more preferably 0.3 to 3.0 parts by mass, based on 100 parts by mass of the component (C).

[0101] (E) Other additives

[0102] The resin composition of the present embodiment may further contain other additives as desired within the scope not impairing the main purpose of the present embodiment, such as carbon black, titanium black, coupling agent, ion trapping agent, leveling agent, antioxidant, defoaming agent, viscosity modifier, flame retardant, colorant, plasticizer, etc. The type and addition amount of each additive are as shown in the conventional method.

[0103] The method for producing the resin composition of the present embodiment is not particularly limited. For example, the components (A) to (C), and the components (D) and (E) and other additives as required are simultaneously or separately introduced into an appropriate mixer, and stirred and mixed to form a uniform composition, whereby the resin composition of the present embodiment can be obtained. The mixer is not particularly limited, and a kneader equipped with a stirring device and a heating device, a Henschel mixer, a three-roll mill, a ball mill, a planetary mixer, a bead mill, etc. can be used. In addition, these devices can also be used in appropriate combination.

[0104] The resin composition thus obtained is thermosetting and can be cured at a low temperature such as 40 to 120°C, preferably 50 to 100°C, more preferably 70 to 90°C, and further preferably 80°C. Under the condition of a temperature of 80°C, it is preferably cured within 4 hours, more preferably within 3 hours, and further preferably within 1 hour. When the curable composition of the present embodiment is used for manufacturing a semiconductor module including components that deteriorate under high-temperature conditions, it is preferably thermally cured at a temperature of 50 to 100°C for 15 minutes to 4 hours, preferably 30 minutes to 2 hours.

[0105] The resin composition of the present embodiment can be used, for example, as an adhesive or a sealing material for fixing, bonding, or protecting components of a semiconductor device or an electronic component to each other, or as a raw material thereof.

[0106] The application method of the resin composition of the present embodiment is not particularly limited. For example, it can be supplied to a desired part such as a substrate by a known printing method, dispensing method, or coating method. As the printing method, inkjet printing, screen printing, lithographic printing, carton printing, metal printing, offset printing, intaglio printing, flexographic printing, etc. can be mentioned, but it is not limited to these. As the dispensing method, methods using an ejection dispenser, an air dispenser, etc. can be mentioned, but it is not limited to these. As the coating method, dip coating, spray coating, bar coater coating, gravure coating, reverse gravure coating, spin coater coating, etc. can be mentioned, but it is not limited to these.

[0107] [Adhesive or Sealing Material]

[0108] The adhesive or sealing material of the second embodiment of the present invention comprises the resin composition of the first embodiment. The adhesive or sealing material can well fix, bond or protect engineering plastics (such as LCP (liquid crystal polymer), polyamide, polycarbonate, etc.), ceramics and metals (such as copper, nickel, etc.), and can be used to fix, bond or protect components constituting semiconductor devices or electronic components. As semiconductor devices or electronic components, for example, HDD, semiconductor elements, sensor modules such as image sensor modules, camera modules, semiconductor modules, integrated circuits, etc. can be cited, but are not limited to these.

[0109] The adhesive or sealing material of this embodiment can be cured under low temperature conditions and therefore has high productivity, and is suitable for use in, for example, manufacturing semiconductor devices and electronic components.

[0110] [Cured product of resin composition, adhesive or sealing material]

[0111] The cured product of the third embodiment of the present invention is a cured product obtained by curing the resin composition of the first embodiment or the adhesive or sealing material of the second embodiment. Depending on the type of (B) inorganic particles, either a conductive cured product or an insulating cured product can be provided.

[0112] "Normal temperature elastic modulus" refers to the degree of rigidity and flexibility at room temperature exhibited by a cured product of a certain resin composition. It can be said that the higher the normal temperature elastic modulus, the higher the rigidity, and the lower the normal temperature elastic modulus, the higher the flexibility. In the present embodiment, when appropriate flexibility is required for the cured product, the normal temperature elastic modulus of the cured product obtained by curing at 80°C for 60 minutes is preferably 0.01 to 8.0 GPa, more preferably 0.1 to 7.0 GPa, and further preferably 0.2 to 6.0 GPa. The normal temperature elastic modulus of the cured product can be adjusted by adjusting the type and amount of the components of the resin composition. For example, when appropriate rigidity is required for the cured product, as the main chain of component (A) contains rigid structures such as biphenyl, naphthalene, and dicyclopentadiene, and the amount of the multifunctional compound as component (A) is increased, there is a tendency for the elastic modulus to become larger. On the other hand, when appropriate flexibility is required for the cured product, the elastic modulus tends to be reduced by including a hydrocarbon group derived from a long-chain alkyl group, a long-chain oxyalkylene group, a polyether, or a dimer acid in the main chain of component (A). The room-temperature elastic modulus can be measured by using a dynamic viscoelasticity measuring device (DMA) (e.g., DMA7100, manufactured by Hitachi High-Tech Science Co., Ltd.) in accordance with JIS C6481 on a sample coating film of a predetermined film thickness obtained by curing the resin composition, as shown in the measurement method in the examples described later.

[0113] [Semiconductor devices, electronic components]

[0114] Since the semiconductor device or electronic component of the fourth embodiment of the present invention includes the cured product of the third embodiment, these semiconductor devices or electronic components have high reliability. Here, the semiconductor device refers to all devices that can function by utilizing semiconductor characteristics, and includes electronic components, semiconductor circuits, modules assembled with them, electronic equipment, etc. Semiconductor devices or electronic components can include, for example, HDDs, semiconductor elements, sensor modules such as image sensor modules, camera modules, semiconductor modules, integrated circuits, etc., but are not limited to these.

[0115] Example

[0116] Hereinafter, the present invention will be further described in detail by way of examples and comparative examples, but the present invention is not limited to these examples. It should be noted that, in the following examples, parts and % represent parts by mass and % by mass unless otherwise specified.

[0117] [Examples 1 to 13, Comparative Examples 1 to 4]

[0118] A resin composition was prepared by mixing prescribed amounts of each component using a three-roll mill according to the formulation shown in Table 1. In Table 1, the amount of each component is expressed in parts by mass (unit: g). The components used in Examples and Comparative Examples are as follows.

[0119] (A) Radically polymerizable curable compound (component (A))

[0120] (A-1): Cyclic trimethylolpropane formal acrylate (product name: Viscoat #200, manufactured by Osaka Organic Chemical Industry Co., Ltd., monofunctional)

[0121] (A-2): Tripropylene glycol diacrylate (product name: TPGDA, manufactured by Daicel-Allnex Co., Ltd., difunctional)

[0122] (A-3): Phosphoric acid-modified acrylate (product name: EBECRYL168, manufactured by Daicel-Allnex Co., Ltd., 1.5 functional)

[0123] (A-4): Urethane acrylate oligomer 1 (product name: UN-6200, manufactured by Negami Industries, Ltd., difunctional)

[0124] (A-5): Urethane acrylate oligomer 2 (product name: MBA-2CZ, manufactured by Negami Industries, Ltd., difunctional)

[0125] (A-6): Urethane acrylate oligomer 3 (product name: UV-3000B, manufactured by Nippon Synthetic Chemical Industry Co., Ltd., difunctional)

[0126] (A-7): Bismaleimide compound (product name: BMI-1500, manufactured by Designer Molecules Inc., difunctional)

[0127] (B) Inorganic particles (component (B))

[0128] - (B1) Conductive particles

[0129] (B1-1): Silver powder 1 (product name: EA79613, manufactured by Metalor Technologies Japan Co., Ltd., average particle size (D50): 7 μm, BET specific surface area: 0.3 m 2 / g, tap density: 5.1g / cm 3 )

[0130] (B1-2): Silver powder 2 (product name: K 79121P, manufactured by Metalor Technologies Japan Co., Ltd., average particle size (D50): 7 μm, BET specific surface area: 2.3 m 2 / g, tap density: 2.7g / cm 3 )

[0131] - (B2) Insulating particles

[0132] (B2-1): Silica particles (product name: SE5200SEE, manufactured by Admatechs Co., Ltd., average particle size (D50): 2 μm)

[0133] (C) an organic peroxide having a dicarbonate structure represented by formula (1) (component (C))

[0134] (C-1): Dihexadecyl peroxydicarbonate (product name: Perkadox24L, manufactured by Nouryon Chemical Co., Ltd., carbon number of R1 and R2: 16 each, weight average molecular weight: 570.88, 10-hour half-life temperature (T10): 48°C)

[0135] (C-2): Dimyristyl peroxydicarbonate (product name: Perkadox 26, manufactured by Nouryon Chemical Co., Ltd., carbon number of R1 and R2: 14 each, weight average molecular weight: 514.78, 10-hour half-life temperature (T10): 41°C)

[0136] (C-3): ditridecyl peroxydicarbonate (manufactured by Alfa Chemical Co., Ltd., carbon number of R1 and R2: 13 each, weight average molecular weight: 486.72)

[0137] (C-4): Distearyl peroxydicarbonate (manufactured by SAGECHEM LIMITED, R 1 and R 2 Number of carbon atoms: 18 each, weight average molecular weight: 626.99)

[0138] ・(C') Organic peroxides other than component (C) (component (C'))

[0139] (C'-1): 1,1,3,3-tetrabutyl peroxydecanoate (product name: Luperox 810, manufactured by ARKEMA Yoshitomi Co., Ltd., weight average molecular weight: 300.5, 10-hour half-life temperature (T10): 44°C)

[0140] (C'-2): bis(1-methyl-1-phenylethyl)=peroxide (product name: PERCUMYL D, manufactured by NOF Corporation, weight average molecular weight: 270.38, 10-hour half-life temperature (T10): 116.4°C)

[0141] (C'-3): bis(4-tert-butylcyclohexyl) peroxydicarbonate (product name: PEROYL TCP, manufactured by NOF Corporation, carbon number of R1 and R2: 10 each, weight average molecular weight: 398.55, 10-hour half-life temperature (T10): 40.8°C)

[0142] (C'-4): di-sec-butyl diperoxydicarbonate (product name: Luperox 225, manufactured by Nouryon Chemical Co., Ltd., carbon number of R1 and R2: 4 each, weight average molecular weight: 234.25, 10-hour half-life temperature (T10): 51°C)

[0143] (D) Inhibitor (component (D))

[0144] (D-1): N-nitroso-N-phenylhydroxylamine aluminum (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.)

[0145] (D-2): p-Benzoquinone (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.)

[0146] [Examples 14 and 15]

[0147] Resin compositions of Examples 14 and 15 were prepared in the same manner as in Example 1, except that the component (C-1) used in Example 1 was replaced by the components (C-3) and (C-4), respectively. The properties of the resin compositions of Examples 14 and 15 and the cured products obtained by curing the resin compositions were measured in the same manner as in Example 1.

[0148] In Examples and Comparative Examples, properties of the resin composition and the cured product obtained by curing the resin composition were measured as follows.

[0149] <80℃60min coating surface curing performance>

[0150] On a glass slide, a 100 μm thick tape was used as a gap, and each resin composition of the embodiment and the comparative example was applied to form a coating film, which was cured at 80°C for 60 minutes. Then, based on whether the components from the resin composition adhered to the fingers, the sample part of the test piece was confirmed to be cured by visual inspection and finger touch. The test piece where the curing of the sample part can be confirmed is set as "○", and the test piece where the curing of the sample surface part cannot be confirmed is set as "×". The results are shown in Table 1.

[0151] <Validity period>

[0152] The viscosity of each resin composition of the embodiment and the comparative example was measured at a rotation speed of 10 rpm immediately after the resin composition was prepared and after the resin composition was placed at room temperature (about 25°C) for a predetermined time. The change ratio of the viscosity of the resin composition after being placed for a predetermined time when the viscosity of the resin composition just prepared was set to 1.0 was calculated and used as the viscosity increase ratio, and the time when the viscosity increase ratio reached 1.5 times or more was used as the pot life of the resin composition (unit: hour). The results are shown in Table 1.

[0153] The pot life of the resin composition is preferably 24 hours or longer, more preferably 48 hours or longer, and even more preferably 72 hours or longer.

[0154] <Normal temperature elastic modulus>

[0155] On a glass slide with Teflon (registered trademark) tape attached, each resin composition of the embodiment and the comparative example was applied in such a manner that the film thickness when cured was 200±50μm to form a coating film, and the resin composition was cured at 80°C for 60 minutes in an air drying oven to obtain a cured product. After peeling the coating film-like cured product from the glass slide with Teflon (registered trademark) tape attached, a 40mm×5mm test piece of the cured product was cut with a cutter to obtain a test piece of the cured product. The cut of the cutter was smoothed with sandpaper. According to JIS C6481, the obtained test piece was measured under the following conditions using a dynamic viscoelasticity measuring device (DMA) (DMA7100, manufactured by Hitachi High-Tech Science Co., Ltd.). The results are shown in Table 1.

[0156] Deformation mode: Tension

[0157] Measurement mode: Ramp

[0158] Frequency: 10Hz

[0159] Strain amplitude: 5μm

[0160] Minimum tension / pressure: 50mN

[0161] Tension / Compression Gain: 1.2

[0162] Initial force amplitude: 50mN

[0163] Mobile waiting time: 8 seconds

[0164] Creep waiting time factor: 0

[0165] Temperature: 25℃.

[0166] The room-temperature elastic modulus of a cured product obtained by curing the resin composition at 80° C. for 60 minutes is preferably 0.01 to 8.0 GPa, more preferably 0.1 to 7.0 GPa, and even more preferably 0.2 to 6.0 GPa.

[0167] <Resistance measurement>

[0168] Two heat-resistant tapes of about 85 to 105 μm thick were pasted in parallel on the glass substrate at an interval of 3 mm, and each conductive resin composition film of 3 mm width × 50 mm length × about 95 μm thickness was printed between the two heat-resistant tapes, and then cured at 80°C for 60 minutes in an air drying oven. The thickness of the obtained cured film was measured using a surface roughness shape measuring machine (model: Surfcom 1500SD-2) manufactured by Tokyo Seimitsu Co., Ltd., and the resistance value was measured using a digital multimeter (model: 2001) manufactured by TFF Keithley Instruments Co., Ltd. The volume resistivity was calculated and used as the specific resistance value. It should be noted that Comparative Example 2 could not be measured. Examples 12 and 13 that do not contain conductive particles were not measured.

[0169] The specific resistance value is preferably less than 10×10 -4 The results are shown in Table 1.

[0170]

[0171] The resin compositions of Examples 1 to 13 can all be cured under the curing conditions of 80° C. and 60 minutes, and have a pot life of more than 48 hours.

[0172] The resin compositions of Comparative Examples 1 to 4, which contain an organic peroxide other than the component (C) instead of the component (C), cannot achieve both low-temperature curability at 80° C. and a long pot life.

[0173] Industrial Applicability

[0174] The present invention is a curable resin composition that can be cured under low temperature conditions and is very useful as an adhesive or sealing material suitable for use in the production of semiconductor devices and electronic parts.

[0175] The disclosure of Japanese Patent Application No. 2022-187039 (filing date: November 24, 2022) is incorporated herein by reference in its entirety.

[0176] All documents, patent applications, and technical standards described in this specification are incorporated herein by reference to the same extent as if each individual document, patent application, and technical standard was specifically and individually described as being incorporated by reference.

Claims

1. A curable resin composition comprising: (A) a free radical polymerizable curable compound; (B) inorganic particles; and (C) an organic peroxide having a dicarbonate structure represented by the following formula (1), In the formula (1), R1 and R2 are each independently an alkyl group having at least 11 carbon atoms.

2. The curable resin composition according to claim 1, wherein The weight average molecular weight of the (C) organic peroxide is 400 or more.

3. The curable resin composition according to claim 1 or 2, wherein The 10-hour half-life temperature of the (C) organic peroxide is 70° C. or less.

4. The curable resin composition according to any one of claims 1 to 3, wherein The content of the (C) organic peroxide is 0.1 to 30 parts by mass based on 100 parts by mass of the (A) radically polymerizable curable compound.

5. The curable resin composition according to any one of claims 1 to 4, wherein The (A) radically polymerizable curable compound includes a (meth)acrylate compound.

6. The curable resin composition according to any one of claims 1 to 5, wherein The (A) radically polymerizable curable compound includes a urethane (meth)acrylate compound.

7. The curable resin composition according to any one of claims 1 to 6, wherein The (A) radically polymerizable curable compound includes a bismaleimide compound.

8. The curable resin composition according to any one of claims 1 to 7, wherein The (B) inorganic particles include conductive particles. 9 . The curable resin composition according to claim 1 , further comprising (D) a polymerization inhibitor. 10 . An adhesive or a sealing material comprising the curable resin composition according to claim 1 . 11 . A cured product obtained by curing the curable resin composition according to claim 1 , or the adhesive or sealing material according to claim 10 .

12. The cured product according to claim 11, wherein The room temperature elastic modulus of the cured product obtained by curing at 80° C. for 60 minutes is 0.01 GPa to 8.0 GPa. 13 . A semiconductor device or an electronic component comprising the cured product according to claim 11 or 12 .

Citation Information

Patent Citations

  • Ultraviolet curable resin composition, cured product thereof, and various kinds of articles derived therefrom

    JP2008184514A

  • Photosensitive resin composition and application thereof

    JP2010117545A

  • Anisotropic conductive adhesive and printed wiring board using the same

    JP2015193725A

  • Conductive resin composition, conductive resin composition for dispensing, die attach agent, and semiconductor device

    JP2016117860A

  • Pre-supply type underfill material, cured product of pre-supply type underfill material, electronic component device, and manufacturing method of electronic component device

    JP2020065063A